(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, opinions are given about the methods and importance of studying the pronunciation of words in the Uzbek language. It is emphasized on the basis of specific examples that the study of the structural features of each national, in particular, Uzbek language words, is one of the current urgent problems. There are several recommendations for studying nouns.